PEMBERDAYAAN MASYARAKAT INDUSTRI: KETERAMPILAN GOLD-ELECTROPLATING BAGI CALON LULUSAN SMA DENGAN PENDEKATAN ANDRAGOGI (ADULT LEARNING) - Doni Pernanda; Roberta Surya Zulfhi (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2026)
A community empowerment program for gold electroplating skills was conducted to enhance Chemistry understanding and practical competence among high school graduates using an andragogy approach. The program targeted 88 students (aged 16-19 years) from two high schools: SMA N 1 Tembilahan (28 participants) and SMA N 1 Tanah Merah (60 participants) on August 26, 2025, and November 10, 2025, respectively. Participants were guided through theoretical learning on electrochemical processes using aqua regia as a gold leaching agent, followed by hands-on practice in electroplating circuits and economic analysis. Results showed high satisfaction rates: 90% very satisfied at Tembilahan and 75% at Tanah Merah. All participants demonstrated practical competence in the gold electroplating process and understood business feasibility. The direct involvement in electrochemical reactions enhanced their understanding of Chemistry concepts, particularly electrochemistry (electroplating), and equipped them with scalable economic skills for entrepreneurship or industrial employment in electroplating sectors, including metal, steel, and automotive industries. This program successfully integrated theoretical knowledge with practical experience, demonstrating how andragogy principles effectively engage adult learners in acquiring economically valuable technical skills. Program pemberdayaan masyarakat untuk keterampilan penyepuhan emas (gold electroplating) dilaksanakan untuk meningkatkan pemahaman Kimia dan kompetensi praktis calon lulusan SMA menggunakan pendekatan andragogi. Program menargetkan 88 siswa (usia 16-19 tahun) dari dua sekolah menengah atas: SMA N 1 Tembilahan (28 peserta) dan SMA N 1 Tanah Merah (60 peserta) masing-masing pada tanggal 26 Agustus 2025 dan 10 November 2025. Peserta dibimbing melalui pembelajaran teori proses elektro-kimia menggunakan aqua regia sebagai agen pelindian emas, diikuti praktik langsung dalam rangkaian penyepuhan dan analisis ekonomi. Hasil menunjukkan tingkat kepuasan tinggi: 90% sangat puas di Tembilahan dan 75% di Tanah Merah. Seluruh peserta menunjukkan kompetensi praktis dalam proses gold electroplating dan memahami kelayakan bisnis. Keterlibatan langsung dalam reaksi elektro-kimia meningkatkan pemahaman konsep Kimia mereka, terutama elektrokimia (electroplating), dan melengkapi mereka dengan keterampilan ekonomi yang dapat dikembangkan untuk wirausaha atau bekerja di industri sektor penyepuhan mencakup industri logam, baja, dan otomotif. Program ini berhasil mengintegrasikan pengetahuan teoretis dengan pengalaman praktis, mendemonstrasikan bagaimana prinsip andragogi secara efektif melibatkan peserta didik dewasa dalam memperoleh keterampilan teknis yang bernilai ekonomis.